Growth and maturity status of young male table tennis players - Coelho-e-Silva, M. J.; Konarski, J. M.; Krzykala, M.; Galas, S.; Beata, P.; Zurek, P.; Faria, J.; Tavares, O. M.; Oliveira, T. G.; Rodrigues, I.; Martinho, D. V.; Valente-Dos-Santos, J.; et al. (Research in Sports Medicine, 2022)
A maturity-associated gradient among adolescent athletes in many sports tends to favour early maturing participants. This study was aimed to describe inter-individual variance in growth and skeletal maturation among male youth table tennis. The sample included 99 players registered in competitive clubs for at least 2 years. Chronological age (CA) ranged 10.00-14.63 years. Stature and body mass were plotted relative to US references. Skeletal age (SA) was estimated with the Fels method. Maturity status was given as SA minus CA. Somatic maturation was derived from predicted age at peak height velocity. Mean values for stature and weight were above the reference medians from 10 to 13 years and at the median in the oldest group. In general, SA was in advance to CA (CA: 12.45 ± 1.28 years; SA: 13.44 ± 2.37 years). The majority of the players were early maturing according to SA (52%) and average maturing based on the somatic indicator (80%). The results suggested that table tennis tends to retain taller and heavier participants who are somewhat advanced in skeletal maturity. Participation in youth table tennis and opportunities to win need to consider age- and maturity-associated variations, particularly regarding bands for competitions.